Geopolitics of technology: A new battleground? - Khan, Khalid; Su, Chi-Wei; Umar, Muhammad; Zhang, Weike (Technological and Economic Development of Economy, 2022)
This study aims to consider the causality between global geopolitical risk (GPR) and technology (TEC) using the rolling window approach. The results reveal that GPR has a significant impact on TEC across different sub-samples. It points out that GPR increases TEC and both are highly integrated and the geopolitical constraints are pivotal to TEC development. On the other hand, TEC leads GPR due to competition between countries for geopolitical dominance and security. The results back the Becker Model, which reveals that divergence of interests between countries drive TEC competition and systematically associated with GPR in a country. The international community should create a mechanism that supports interoperability and the states should pay attention to TECs that are critical to economic and strategic interests in the long run. Moreover, the states could enhance cooperation with the private sector which is an important determinant. First published online 02 February 2022